TIPOLOGI MANAJEMEN TRADISIONAL DAN MODERN DALAM PENDIDIKAN ISLAM - Zainuddin Fanani (JURNAL PUSAKA, 2018)
Management of an educational institution is the main activity that distinguishes one institution from another in providing services to humans in the field of education. The success of educational institutions in achieving the goals of education and social responsibility is largely determined by the functions carried out by every education manager. Therefore an education manager is required to master management practices. In the Islamic boarding school leadership environment is still held by the clerics but in organizing there are parts themselves, so that the movement and progress of the development of the pesantren will be better. The combination of the salaf and modern management system will result in the management of Islamic education that is very reliable and can keep up with the times, and does not miss other countries in the education system, even better and better.